A phase I randomized, double‐blind, single subcutaneous dose escalation study to determine the safety, tolerability, and pharmacokinetics of rezafungin in healthy adult subjects. Issue 7 (4th May 2022) - Gu, Kenan; Ruff, Dennis; Key, Cassandra; Thompson, Marissa; Jiang, Shoshanna; Sandison, Taylor; Flanagan, Shawn
Abstract: Rezafungin is a novel echinocandin being developed for the treatment and prevention of invasive fungal infections. The objectives of this randomized, double‐blind study in healthy adults were to determine the safety, tolerability, and pharmacokinetics of rezafungin after subcutaneous (s.c.) administration. The study design consisted of six sequential cohorts of eight subjects, except for the first cohort with four subjects. The subjects were randomized in a 3:1 ratio of rezafungin to placebo and were to receive a single dose of 1, 10, 30, 60, 100, or 200 mg. The most common adverse events (AEs) were increased alanine aminotransferase and sinus bradycardia (unsolicited) and erythema at the injection site (solicited). Unsolicited AEs were generally mild to moderate and not rezafungin‐related. Although the study was terminated after the 10 mg dose cohort due to concerns of potential increased severity of injection site reactions, no predetermined dose escalation halting criteria were met. Following the 10 mg single s.c. dose of rezafungin ( n = 6), the geometric mean (GM) maximum concentration ( C max ) was 105.0 ng/ml and the median time to C max was 144 h. The GM area under the concentration‐time curve was 32, 770 ng*h/ml. The median estimated terminal half‐life was 193 h. The GM apparent oral clearance was 0.255 L/h and the GM apparent volume of distribution was 68.5 L. This study demonstrates that a single s.c. dose of rezafungin in healthy adult subjects: (1) did not result in serious AEs, death, or withdrawal from the study due to an AE; and (2) produced a pharmacokinetic profile with long exposure period postadministration. In an effort to reduce the occurrence of injection site reactions, a re‐evaluation of the rezafungin s.c. formulation could be considered in the future.